Percontohan Alat Pembakar Sampah Minim Asap Sederhana Dan Tempat Sampah Terpilah Di Desa Sanrobone Kabupaten Takalar - Liliskarlina, Liliskarlina; Hamzah, Hadzmawaty; Hasan, Nurul Wahidah (Patria Artha Journal of Community (PKM), 2025)
Waste management in rural areas remains a critical challenge, particularly due to open burning practices that cause air pollution and health risks. Sanrobone Village in Takalar Regency faces problems of household waste accumulation without an adequate waste management system. This community service project aims to introduce a simple low-smoke waste incinerator and segregated waste bins as practical, affordable, and environmentally friendly solutions. The activities included field surveys, socialization, community training, construction of low-smoke incinerators, and installation of color-coded waste bins at strategic points. The results indicate improved community awareness in waste sorting and correct incinerator use, reducing smoke emissions by approximately 70%. The program also formed a village waste management group as an initial step toward sustainable waste handling. This pilot initiative is expected to serve as a replicable model for other villages to promote clean and healthy community environments.